GOOGLE EARTH INTEGRATION IN LEARNING: A NARRATIVE REVIEW - J. Priyanto Widodo; Nurmida Catherine Sitompul; Iman Subekti; Linda Bustan; Anggun Purnomo Arbi (Widya Mandala Surabaya Catholic University, 2025)
Technology integration in education is increasingly developing, including the use of Google Earth as an interactive learning medium. However, its utilization in Indonesia is still limited due to the lack of teacher training and access to technology. This research is intended to analyze the trend of Google Earth usage in learning through narrative review method. The study reviewed related literature to identify the fields of study that use it the most, the research methods applied, and the benefits and challenges found. The results show that Google Earth improves learning motivation, student engagement and spatial understanding. However, research is still dominated by short-term experimental methods, so longitudinal studies are needed to measure its impact in the long term. The implications of this research highlight the need for teacher training, supporting policy development, and further exploration in STEM and vocational education.